Kompensasi Karyawan dan Budaya Perusahaan terhadap Motivasi Kerja - Ahsya Ainus Shifak; Yudithia Dian Putra; Ilyas Indra (Universitas Islam Kadiri, 2022)
This study aims to measure the extent to which compensation and work culture affect work motivation. This study finds new facts where compensation is an important factor in encouraging employee motivation. In addition, this study also reveals a new fact that a work culture consisting of discipline, good cooperation, organizational communication, identity in the form of uniforms is also a factor in employee work motivation. The method used in this research is descriptive quantitative with independent variables X1 Compensation and X2 Work Culture. The dependent variable (Y) of this study is work motivation. The results of the F test showed that the independent variables had a simultaneous effect on the dependent variable with a significance value of 0.037 or less than 0.05. Meanwhile, the results of the t-test or partial shows that both variables X1 and X2 have an effect on variable Y. The significance value of X1 is 0.034 and X2 is 0.025 or less than 0.05.